Hygiene and Sanitation Analysis in Ibu Wanti Canteen Faculty of Business Economics Mulawarman University - Banin, Maghfirotin Marta; Kristina, Vienti Elisa; Utoro, Panggulu Ahmad Ramadhani; Andriyani, Yulian; Rohmah, Miftakhur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Sanitation hygiene controls food, people, places, or equipment contamination risks to ensure food safety. An initial survey at Bu Wanti Canteen, Mulawarman University, revealed issues with food processing and inadequate sanitation facilities, including improper waste disposal and unclean eating areas. A Participatory Action Research study showed that the canteen's hygiene and sanitation initially scored 60 out of 70 (86%), falling below A1 catering standards. However, after receiving assistance, the score improved to 65 out of 70 (93%), resulting in a cleaner and healthier environment that meets hygiene standards.